Who were the Hyksos? Challenging traditional narratives using strontium isotope (87Sr/86Sr) analysis of human remains from ancient Egypt. - Chris Stantis; Arwa Kharobi; Nina Maaranen; Geoff M Nowell; Manfred Bietak; Silvia Prell; Holger Schutkowski (PLoS ONE, 2020)
A foreign dynasty, known as the Hyksos, ruled parts of Egypt between c. 1638-1530 BCE. Their origins are thought to be rooted in the Near East, which is supported by architectural features and grave accoutrements of Tell el-Dabca. In this former Hyksos capital in the Eastern Nile Delta, burial culture is characterized by a blend of Egyptian and Near Eastern elements. However, investigations are still ongoing as to where the Hyksos came from and how they rose to power. The aim of this study is to elucidate the question of possible provenience. We present the results of strontium isotope (87Sr/86Sr) ratios of human tooth enamel (n = 75) from Tell el-Dabca, focusing on comparing pre- and during Hyksos rule and sex-based differences. An influx of non-locals can be observed in the pre-Hyksos period (12th and 13th Dynasties, c. 1991-1649 BCE) during the constitution of this important harbor town, while the number of individuals already born in the Delta is larger during the Hyksos period. This is consistent with the supposition that, while the ruling class had Near Eastern origins, the Hyksos' rise to power was not the result of an invasion, as popularly theorized, but an internal dominance and takeover of foreign elite. There is a preponderance of non-local females suggesting patrilocal residence. We discuss our findings against the current evidence of material culture and historiography, but more investigation in Near Eastern comparative sites has to be conducted to narrow our future search for the actual origins of the Hyksos.